(untitled) (Research, Society and Development, 2021)
Objective: to describe the importance of caring for arteriovenous fistula in patients undergoing hemodialysis as renal replacement therapy. Methodology: The study consisted of an integrative literature review in a qualitative and descriptive metodology, with bibliographic research in the databases of articles in the health area, such as PubMed, Scielo and LILACS, in the period between 2015 and 2020. The keywords used were “hemodialysis”, “arteriovenous fistula” and “nursing care” as well as their English counterparts. Exclusion criteria: articles published before 2015 that did not address fistula care. From this set of keywords, filters were defined that served as inclusion criteria: articles available in full, in Portuguese and English, from 2015 to 2021 and that had affinity with the theme. Results: During the research, 132 publications were identified, which after applying the inclusion criteria, remained 15 articles. The literature points out that AVF should be the first choice when it comes to vascular access for hemodialysis, with studies indicating that at least 50% of patients on dialysis should use this access. Distal AVFs in the upper limbs are the first option, like the radiocephalic one, as they leave the proximal veins for a possible need for a new access in the future. Hemodialysis treatment prolongs the life expectancy given to these patients who, with the continuous use of the AVF, suffer from depletion of the venous system of the upper limb, requiring the preparation of exceptional AVFs in veins from other parts of the body, such as the axillary-jugular vein, the axillary-axillary, saphenous vein loops in the lower limbs, or through prostheses, such as femorofemoral loops, axillary-axillary collar. Conclusion: The vascular accesses for hemodialysis are far from being completely perfected and recent studies show a range of alternatives for making and maintaining the accesses.